Photoactivatable dihydroalkaloids for cancer cell imaging and chemotherapy with high spatiotemporal resolution. Issue 10 (5th August 2020) - Ling, Xia; Huang, Letao; Li, Youzhen; Wan, Qing; Wang, Zhiming; Qin, Anjun; Gao, Meng; Tang, Ben Zhong
Abstract : A photoactivatable strategy is proposed for precise cancer therapy based on photooxidative dehydrogenation reaction, which is demonstrated with the natural dihydroalkaloids of DHCHE and DHSAN as an example. Abstract : Chemotherapeutics with systemic administration usually suffer from low treatment efficacy and off-target toxicity. On the contrary, photoactivatable cancer theranostics can achieve image-guided precise control of therapeutic dose and location. However, the conventional photoactivatable chemotherapeutics usually require decoration of the chemotherapeutics with additional photo-responsive groups through tedious synthetic procedures, which can lead to undesirable toxic byproducts and seriously restrict their applications. Herein, we propose a new strategy for photoactivatable cancer theranostics based on a photooxidative dehydrogenation reaction, which is only associated with water as the byproduct. To demonstrate the power of this strategy, we utilized the natural dihydrobenzo[ c ]phenanthridine alkaloids of DHCHE and DHSAN as photoactivatable theranostics to achieve the selective imaging and killing of cancer cells by in situ transformation into nucleus-targeted CHE and SAN under light irradiation. Notably, CHE features aggregation-induced emission (AIE) characteristics, which can be used for the precise control of the photoactivatable therapeutic dose. This photoactivatable strategy based on a photooxidative dehydrogenation reaction is thus promising for precise cancer treatment in the clinic.